Bibliometric analysis of global research trends between gut microbiota and breast cancer: from 2013 to 2023 - Deng, Xianguang; Yang, Hua; Tian, Lingjia; Ling, Jie; Ruan, Hui; Ge, Anqi; Liu, Lifang; Fan, Hongqiao (Frontiers in Microbiology, 2024)
Background: Breast cancer is the most prevalent cancer globally and is associated with significant mortality. Recent research has provided crucial insights into the role of gut microbiota in the onset and progression of breast cancer, confirming its impact on the disease's management. Despite numerous studies exploring this relationship, there is a lack of comprehensive bibliometric analyses to outline the field's current state and emerging trends. This study aims to fill that gap by analyzing key research directions and identifying emerging hotspots.Method: Publications from 2013 to 2023 were retrieved from the Web of Science Core Collection database. The VOSviewer, R language and SCImago Graphica software were utilized to analyze and visualize the volume of publications, countries/regions, institutions, authors, and keywords in this field.Results: A total of 515 publications were included in this study. The journal Cancers was identified as the most prolific, contributing 21 papers. The United States and China were the leading contributors to this field. The University of Alabama at Birmingham was the most productive institution. Peter Bai published the most papers, while James J. Goedert was the most cited author.Analysis of highly cited literature and keyword clustering confirmed a close relationship between gut microbiota and breast cancer. Keywords such as "metabolomics" and "probiotics" have been prominently highlighted in the keyword analysis, indicating future research hotspots in exploring the interaction between metabolites in the breast cancer microenvironment and gut microbiota.Additionally, these keywords suggest significant interest in the therapeutic potential of probiotics for breast cancer treatment.Research on the relationship between gut microbiota and breast cancer is expanding.Attention should be focused on understanding the mechanisms of their interaction, particularly the metabolite-microbiota-breast cancer crosstalk. These insights have the potential to advance prevention, diagnosis, and treatment strategies for breast cancer. This bibliometric study provides a comprehensive assessment of the current state and future trends of research in this field, offering valuable perspectives for future studies on gut microbiota and breast cancer.